Risk-taking behavior, competition, diversification and performance of frontier and emerging economy banks - Nicholas Addai Boamah; Augustine Boakye-Dankwa; Emmanuel Opoku (Asian Journal of Economics and Banking (AJEB), 2022)
Purpose - The study examines the dynamic association between competition, risk-taking, performance and income diversification of frontier and emerging economy (FEE) banks. It additionally, explores the effect of banking sector depth and economic performance on the level of competition, performance and risk-taking behavior of banks in these economies. Design/methodology/approach - The paper adopts a panel vector auto-regressive technique and collects data across ninety (90) FEEs. Findings - The paper finds that competition increases with improvement in the depth of the banking sector, a surge in risk-taking behavior and the adoption of focused strategy by banks. Similarly, income diversification activities are driven by competition, banking sector depth, the state of the economy and bank performance. Additionally, risk-taking behavior, banking sector depth and the state of the economy are relevant in describing bank performance. Also, risk-taking behavior is influenced by bank performance, banking sector depth and economic growth. Originality/value - The evidence indicates that although competition improves banking sector health, excessive competition and non-competitive banking environment constrain banks' performance and stability.
Keywords: 330; Income diversification; Emerging markets; Bank stability; Moral hazard; Banks intermediation